Physical and Structural Properties of Sm3+ Doped Phosphate Glasses. Issue 1 (12th February 2021) - Rajagukguk, Juniastel; Harahap, Nursaida; Rahmaniar; Situmorang, Rappel; Hakim S, Abd.; Sunaryono
Abstract: Abstract: In this research, the glasses were made with composition (70-x) P2 O5 - 10Bi2 O3 - 10Na2 O - 10Gd2 O3 - xSm2 O3 (with x = 0; 0.05; 0, 1; 0, 5; 1.0; 3.0 mol%). Molar volume, polar radius and inter nuclear distance decreases with increasing concentration Sm 3+ in phosphate glass. However the refractive index, susceptibility of the oxide ion, polarizability (α) and reflection loss does not change in value. XRD diffraction shows that the patterns shape of the glasses spectrum are found no sharp peaks along the diffraction angle observation area (2θ). This shows that the concentration of Sm 3+ ions does not affect the diffraction pattern of Sm: phosphate glass. The strongest FTIR spectrum is archieved PBNaG: Sm5 galss with wavenumber 871 cm −1 .